From the Theatrical Event to Paper: Rabinal Achí - Paniagua, Carlos (2018)
This article analyzes the cultural implications of the placement, translation and textual recovery of Rabinal Achí, with European-oriented genres, instruments and principles. The different historical periods of this cultural process are studied along with their actors. Based on theater discourse, certain reflections are presented concerning the relation between hegemonic culture and subaltern culture.